Verifying a new historical stage in the ethics of communication: second generation ethics codes - Aznar, Hugo; Mercado-Sáez, María Teresa; Álvarez-Villa, Àngels (Frontiers in Communication, 2024)
Throughout the 20th century, most of the world's countries and international journalistic organizations adopted codes of journalistic ethics with general principles governing the profession. In the 21st century, a significant number of proposals have emerged offering new ethics recommendations relating to the treatment of issues such as gender violence, disability, the environment and climate change, among other matters. The aim of this research is to confirm that we are faced with a second generation of ethics codes or guidelines for social communication. This study, based on the content analysis of 53 guides published in Spain on the three subject areas mentioned, shows the emergence of these codes from 1999 onwards, the existence of common features in relation to their endorsement, their structure, their dissemination and monitoring, and the widespread participation of individuals, experts and groups not professionally related to the field of communication in their promotion or implementation, which is evidence of what we call the social self-regulation of communication and represents the main novelty in this new stage of communication ethics.